2012
DOI: 10.1073/pnas.1201627109
|View full text |Cite
|
Sign up to set email alerts
|

Castor oil induces laxation and uterus contraction via ricinoleic acid activating prostaglandin EP 3 receptors

Abstract: Castor oil is one of the oldest drugs. When given orally, it has a laxative effect and induces labor in pregnant females. The effects of castor oil are mediated by ricinoleic acid, a hydroxylated fatty acid released from castor oil by intestinal lipases. Despite the wide-spread use of castor oil in conventional and folk medicine, the molecular mechanism by which ricinoleic acid acts remains unknown. Here we show that the EP 3 prostanoid receptor is specifically activated by ricinoleic acid and that it mediates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
127
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(140 citation statements)
references
References 41 publications
(47 reference statements)
3
127
0
3
Order By: Relevance
“…These results are in agreement with Ramakrishna et al (1994), Qnais et al (2007) and Sorin et al (2012) who confirmed delay castor oil-induced diarrhoea as a result to inhibition of prostaglandin biosynthesis.…”
Section: Advances In Animal and Veterinary Sciences March 2016 | Volusupporting
confidence: 81%
“…These results are in agreement with Ramakrishna et al (1994), Qnais et al (2007) and Sorin et al (2012) who confirmed delay castor oil-induced diarrhoea as a result to inhibition of prostaglandin biosynthesis.…”
Section: Advances In Animal and Veterinary Sciences March 2016 | Volusupporting
confidence: 81%
“…Castor oil produces diarrhoea due to its active metabolite, a ricinoleic acid which is liberated by the action of lipases in the upper part of the small intestine [34]. It mediates its action by binding to EP3 prostanoid receptors on smooth muscle cells [35] and facilitates the accumulation of fluid in the intestine by inhibiting absorption and enhancing secretion of fluid and electrolytes [36]. Furthermore, this metabolite also alters the motility of GI smooth muscles [37].…”
Section: Discussionmentioning
confidence: 99%
“…Castor oil, an irritant laxative, is thought to produce diarrhoea by being hydrolysed in the upper small intestine to ricinoleic acid which exerts its effects by irritating the mucosa of the gastrointestinal tract, resulting in an increase in intestinal motility (Altman, 2001 ). Fwthermore, ricinoleic acid has been shown to diminish the permeability of sodiun and chloride ions and also stimulate the release of prostaglandin, known to cause diarrhoea (Tunaru et al, 2012;Zavala et al, 1998). In addition, the works of Capasso et al (1994) and Mascolo et al (1994), on the effect of NG-nitro-L-arginine methyl ester, an inhibitor of Nitric Oxide (NO) synthase, on the dissociation of castor oil-induced diarrhoea and mucosal injwy inrat, showed that nitric oxide may mediate castor oil-induced diarrhoea.…”
Section: Discussionmentioning
confidence: 99%